Non contiguous-finished genome sequence and description of Peptoniphilus timonensis sp. nov. Issue 1 (July 2012) - Mishra, Ajay; Lagier, Jean-Christophe; Robert, Catherine; Raoult, Didier; Fournier, Pierre-Edouard
Abstract Peptoniphilus timonensis strain JC401T sp. nov. is the type strain ofP. timonensis sp. nov., a new species within thePeptoniphilus genus. This strain, whose genome is described here, was isolated from the fecal flora of a healthy patient.P. timonensis is an obligate Gram-positive anaerobic coccus. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 1, 758, 598 bp long genome (1 chromosome, no plasmid) contains 1, 922 protein-coding and 22 RNA genes, including 5 rRNA genes.